Kebijakan Pemenuhan Kebutuhan Minyak Cina di Venezuela - , RACHMAT ALEM FINANDY; , Dr. Nur Rachmat Yuliantoro, MA(IR) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Since 1979, China has moved its core policies to be more open and liberalized. Liberalization which has happened in China caused danger in energy security and increased its oil needs. To face this danger, China produced several policies to secure supply from other countries. China focused its policies to a several developing countries which have huge amount of oil reserve but still need financial support to develop their country. One of them is Venezuela, where China has been implementing FDI and policy lending since 1997 to secure supplies until now. Those policies seem effective for both countries. China can secure its oil supplies and Venezuela can get financial support without a heavy political terms.